Revealing the evolution of behavioral activation research trends over two decades through keyword network analysis - Sung-Min Son; Mo-Se Hwang; Yeon-Joo Nam; Kyu-Ho Jeong; June-Ho Seo; Tae Hui Kim (PLoS ONE, 2025)
Backgrounds Behavioral activation (BA) is recognized as an evidence-based therapy for depression and other mental health conditions. Using meta-analysis and systematic literature review to analyze the research trends is helpful, but it has limitations in understanding the flow and development of BA research. Purpose This study aims to analyze BA research trends using keyword network analysis. Methods The study examined network characteristics, centrality, and cohesion by conducting Keyword network analysis (KNA) on BA -related studies from 2003 to 2023. The research was divided into two periods: 2003–2012 and 2013–2023. Results The analysis revealed an increase in the number of keywords from 26 in the first period to in the second, along with a rise in average degree and keyword links. Notably, cancer research surged during the second period. In terms of centrality, the maximum value rose in the second period, with “Depression” maintaining the highest centrality in both periods. For eigenvector centrality, “Older adult” ranked highest in the first period, while “Psycho-oncology” took the lead in the second. Cohesion analysis showed that in the first period, “Depression” was linked to older adult inpatient care, dealing with issues like “Complicated bereavement,” “Posttraumatic stress disorder,” and “Cancer,” as well as serving as a bridge for depression and smoking cessation. In the second period, the scope of “Depression” expanded to include older adult, university students, and children, with a focus on emotional variables, social support, and non-face-to-face interventions. Conclusions This study sheds light on the evolving landscape of research on BA therapy, highlighting its continuous expansion in addressing depression across diverse populations and settings. Our study is the first to provide a comprehensive overview of the research keywords over the past two decades, offering a knowledge map and flow. This contributes to facilitating practical application in clinical settings and understanding research trends related to BA therapy.